Gonzo [videorecording (DVD)] : the life and work of Dr. Hunter S. Thompson - Thompson, Hunter S.; Gibney, Alex; Depp, Johnny (Magnolia Home Entertainment, 2008)
Traces Dr. Thompson's life from his travels with the Hell's Angels, through his various Wild Turkey & drug ingested episodes in politics and righting the wrongs of society.